Are impacts of renewable energy and globalization on carbon neutrality targets asymmetric in South Africa? A reconsideration using nonlinear ARDL approach - Abu-Goodman, Maryam; Gungor, Hasan; Usman, Ojonugwa (Springer Heidelberg, 2023)
In this paper, we deviate from the existing literature by disentangling the independent variables into their positive and negative changes to capture asymmetric and dynamic multiplier effects of renewable energy and globalization on carbon neutrality targets within the framework of the autoregressive distributed lag (ARDL) model. In doing this, the paper uses South African data for the period 1990 to 2018 and the results show that CO2 emissions respond differently to the positive and negative shocks in renewable energy, globalization, and economic growth. The effect of a positive shock in economic growth is inelastic and positively related to CO2 emissions while a negative shock in economic growth has an elastic and negative effect on CO2 emissions. These results hold for both long-run and short-run periods. In the case of globalization, the positive shock increases CO2 emissions while the negative shock decreases CO2 emissions; although the long-run effect of a negative shock is elastic and insignificant while the short-run negative shock exerts an inelastic and significant effect on CO2 emissions. Furthermore, both the upward and downward shocks in renewable energy consumption transmit a negative effect on CO2 emissions in the long-run and short-run periods. Therefore, the paper suggests among others that to effectively decarbonize the South African economy, the use of subsidies, tax credits, tax holidays, and a host of others on green energy activities need to be enhanced as incentives for promoting cleaner energy production and consumption.
Keywords: Renewable energy; Globalization; Carbon neutrality; Nonlinear cointegration test; South Africa